SOCIAL FACTORS AFFECTING LONGEVITY (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
This article analyzes various factors of longevity. Factors affecting longevity, in particular, sports and interesting activities, health and spirituality, walking in a cheerful mood, keeping clean, getting knowledge, etc., are discussed in detail. The final part contains a summary and a list of used literature.